Production Process Monitoring System for RFID-Based SMEs and the Internet of Things - Sipurba, Iguh; Widya Sari, Marti; Hardyanto, R. Hafid; Harry Pratisto, Eko (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2023)
Micro, Small, and Medium Enterprises (UMKM ) illustrates business being run either by private, home households, as well as business entities size small. this venture's own role is important in the growth and industry of a country. In these global economic times, In this case, MSMEs are demanded to carry out replacement To use upgrade energy it's competitive. One aspect that means what you want to ensure energy MSME competitiveness is technology information ( IT ). Adana Sugar Ants " is one of the UMKM which is located in Penggung Hamlet, RT.70/RW.21, Hargorejo , Kokap , Kulon Progo , Yogyakarta. Problems faced by SMEs Adana Sugar Ants are many get quota excess orders for certain events like celebration day large and delivery of goods throughout Indonesia, namely the checking process goods still production done manually with record in the book so that needs a long time and thoroughness by personnel. The objective of the study This is designing tools that simplify the checking process of goods production. So that from study This produces A Production Process Monitoring System for RFID- Based SMEs and the Internet of Things.